A review of mineral precipitation and effective scale inhibition methods at geothermal power plants in West Anatolia (Turkey). (July 2019) - Tut Haklıdır, Füsun S.; Özen Balaban, Tuğbanur
Highlights: In this study, scale precipitation tendency of high temperature geothermal fields are investigated. Thus, the most important geothermal fields, which of them are still used for geothermal power production by different thermodynamic cycle are selected and available hydrochemistry data collected from different studies for these fields. In this study saturation indices were calculated in different temperatures from 50 °C to 250 °C for the selected minerals by using chemical equilibrium modeling of PhreeqC software (Parkhurst and Appelo, 1999 ) for the selected wells from high temperatures geothermal fields in Western Anatolia (Turkey). Quartz and chalcedony show same curve for the thermal waters. These minerals are generally supersaturated below 200 °C and below 135 °C, respectively. These thermal waters are supersaturated below 75 °C with amorphous silica except KD-20 which is undersaturated at all temperatures. In binary systems, thermal waters are supersaturated at temperatures below 160°C with respect to minerals such as quartz and chalcedony. For the selected ORC-binary type power plant for this study, calcite may precipitate in the bore hole and throughout the system. Abstract: In water-dominated reservoirs, binary and flash cycle geothermal power systems are widely used for power generation at moderate or moderate-high reservoir temperatures. For effective management of both energy systems, it is critical to understand the effects of controlling pressure in different sections of a power plant as well as temperature changes and the pH levels of geothermal fluids. For advanced (multi-flash or flash + binary systems) systems, although the expectation of energy efficiency is higher than for flash and binary systems, the management of these systems is more complex because of high reservoir temperatures and multi-separation processes. These multi-steam separations result in dramatic pressure and temperature drops for geothermal fluids after each separation stage. Depending on the geothermal reservoir rocks, water-rock interaction can be inferred and possible scale types may be predicted through water-modeling programs. Based on this information, suitable inhibitors may be suggested after short-term field tests prior to start up processes for geothermal power plants. Western Anatolia has important high-medium geothermal systems that are suitable for power production, depending on large graben structures in the Aegean Extensional Zone. Geothermal power plants (Turkey) are generally designed as binary and flash types, based on the reservoir temperatures (in Germencik-Aydın, Kızıldere-Denizli, Alaşehir-Manisa regions etc.) in Western Anatolia. The scale types may change with respect to geothermal fields even if they are in close proximity to each other. At the same time, in addition to specific scale types, some minerals are commonly found across each of the geothermal fields. The most important scale types in production wells and lines as well as surface equipment are carbonate minerals such as calcite and aragonite. In addition, silica minerals also tend to form scale, up to 150 ⁰C. Scale types in reinjection lines and wells have been commonly identified as celestine, strontium and barite minerals mixed with silica and carbonates in some geothermal power plants. But these scale types also differ within the same reservoir, with well depth. Scale prevention inhibitors and inhibitor systems with different chemical properties are generally used for anti-scaling. Chemical inhibitor performance and mineral precipitation can be monitored both periodically chemical analysis and also using steel control coupons, which are put in at critical pressure drop points along pipelines. Controlling re-injection temperatures and pH levels have had success for anti-scaling. This study is mainly focused on mineral precipitation conditions and the most effective scale inhibition applications in different type geothermal power plants in Western Anatolia.